Importancia del folklore musical como práctica educativa - Arévalo, Azahara (Revista Electrónica de LEEME, 2009)
Educational society of today should reflect on the importance of musical folklore as an educative practice. This paper contents a reflection about folklore and different educative practices taking as examples some musical pieces from Jaen’ Song Book. These kinds of practices are essential since they develop the quality of the learning process in general and the learning of music in particular. Nowadays, the school is the unifier mean for the reappraisal, communication and transmission of the folklore of our culture. Recovering our folklore is a task that depends on every member of the community and it can be possible through the updating of these musical pieces to the new social changes and its possible spreading through the media. Jaen’ Song Book may constitute a mean for promoting its folklore among students of this province. The learning of this repertoire may also serve as an open door to the World to know the labor that is done in our schools. This paper tries to make teachers conscious that the use of folk materials may improve the learning of music as well as it may unfold a new way for future didactic, cultural and anthropological researches.